2013
DOI: 10.1155/2013/174523
|View full text |Cite
|
Sign up to set email alerts
|

Toxicity Assessment of Buprofezin, Lufenuron, and Triflumuron to the EarthwormAporrectodea caliginosa

Abstract: Earthworms are particularly important soil macroinvertebrates and are often used in assessing the general impact of pesticide pollution in soil. The present study was conducted in order to investigate the toxicity of three insect growth regulators (IGRs) buprofezin, lufenuron, and triflumuron, at different application rates and exposure times toward mature earthworms Aporrectodea caliginosa. The effects of these pesticides on the growth rate in relation to the activities of acetylcholinesterase (AChE) and glut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 36 publications
0
5
0
Order By: Relevance
“…The negative influence of HF+ on the earthworm population in relation to HF− on faba bean fields was apparent in the decrease in individual density and their biomass. Many authors reported a reduction in growth, biomass loss, decreased cocoon production or higher mortality after pesticide application [75][76][77][78][79]. Biomass reduction may be an effect of reduced food intake as a strategy to avoid contamination.…”
Section: Earthworm Density and Biomassmentioning
confidence: 99%
“…The negative influence of HF+ on the earthworm population in relation to HF− on faba bean fields was apparent in the decrease in individual density and their biomass. Many authors reported a reduction in growth, biomass loss, decreased cocoon production or higher mortality after pesticide application [75][76][77][78][79]. Biomass reduction may be an effect of reduced food intake as a strategy to avoid contamination.…”
Section: Earthworm Density and Biomassmentioning
confidence: 99%
“…Similar findings were also reported by Izawa et al (1985) who found that the death of Nilaparvata lugens nymphs α treated with buprofezin was attributed to the chitin synthesis inhibitors act during metamorphosis which causes abortive molting. Badawy et al (2013) noted that a significant growth inhibition on the earthworm, Aporrectodea caliginosa, was also seen when exposed to buprofezin and triflumuron. Buprofezin and triflumuron are chitin synthesis inhibitors, act by interfering with chitin synthesis.…”
Section: Resultsmentioning
confidence: 99%
“…IGRs differ widely from the commonly used insecticides, as they exert their insecticidal effects through their influence on development, metamorphosis and reproduction of the target insects by disrupting the normal activity of the endocrine system (Khan, 2016;Dhadialla et al, 1998;Retnakaran et al, 1985;Khatun et al, 2017;Khatter, 2015). These compounds have been tested successfully against several insect species namely, the papaya mealybug Paracoccus marginatus (Khan, 2016); the cotton leaf worm Spodoptera littoralis (Khatter, 2015;Nasr et al, 2010); the brown planthopper Nilaparvata lugens (Kanaoka et al, 1996;Uchida et al, 1985;Izawa et al, 1985); the rice weevil Sitophilus oryzae (Das, 2013;Merzendorfer & Zimoch, 2003); the earthworm Aporrectodea caliginosa (Badawy et al, 2013); brinjal shoot and fruit borer Leucinodes orbonalis (Das & Islam, 2014); the sweet potato whitefly Bemisia tabaci (Ishaaya et al, 1998); and the Colorado potato beetle Leptinotarsa decemlineata (Karimzadeh et al, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…In the fauna of soil-dwelling invertebrates, earthworms are more significant organisms (Fouad et al 2023). Several studies from a long time ago have reported on their favourable effects in the agricultural soils (Badawy et al 2013;Fouad 2021Fouad , et al 2023.…”
Section: Introductionmentioning
confidence: 99%